Cardiac electric activity of1-(2-[(6-methoxyl)-naphthylmethyl])-1-methyl-N-piperidinylacethyl-6,7-dimethoxyl-1,2,3,4-tetrahydroisoquinoline in SHR and WKY rats. - Dong Hui; Liang Zi-Jun; Yang Zao-Chen (Acta Pharmacologica Sinica; Vol 14, No 6 (November 1993): Acta Pharmacologica Sinica, 2016)
1-(2-[(6-Methoxyl)-naphthylmethyl)])-1-methyl-N-piperidinylacethyl -6,7-dimethoxyl-1,2,3,4-tetrahydroisoquinoline (CPU-23), a substituted tetrahydroisoquinoline, reduced the voltages of P wave and J point, prolonged PR interval, and slowed sinus rhythm of ECG in spontaneously hypertensive rats (SHR) and age-matched normotensive WKY rats. The effects of CPU-23 on cardiac electric activity were stronger in SHR than in WKY rats (P < 0.05 or P < 0.01). The results suggest that CPU-23 have a calcium antagonistic activity on rat hearts and that calcium antagonists may exert a stronger inhibition of the cardiac electric activity in hypertensive rats than in normotensive rats.